Analysis of Henbuk Startup Value Using a Scorecard Assessment Method - Estiyanti, Ni Made; Puji Lestari, Ni Kadek; Pramesti Dwi Putri, I Gst. Agung; Máté, Domicián (International Journal of Engineering and Management Sciences, 2024)
This study aims to determine the valuation value of Henbuk's startup by conducting qualitative and quantitative analyses. Henbuk is a startup engaged in e-commerce. The Henbuk startup is currently in the initial funding stage, and the founders are opening opportunities for investors, which can later support operational and development activities. In obtaining funding from investors, the Henbuk startup requires an initial assessment of the company's value. The score assessment consists of several indicators, e.g., quality of the founder and team, opportunity size, product and technology, competition, marketing, sales and partnerships, and the need for additional investment. The results of the value assessment are obtained by using the Scorecard Assessment Method. The results of this study may help to determine the real value of other start-ups for the investors in the future.